Attitudes Toward Physical Activity According to Weight Status Among Schoolchildren in Sousse, Tunisia - Maatoug, Jihene (Health Serv Res Manag Epidemiol, 2015)
AIM: To investigate differences in attitude toward physical activity in normal-weight, overweight, and obese adolescents. MATERIALS AND METHODS: We conducted a cross-sectional survey carried out in 2009/2010. It concerned randomly selected schoolchildren of colleges of Sousse in seventh and ninth grade. The sample was composed of 4003 schoolchildren. A questionnaire was used to evaluate habits and perception of physical activity, and we took anthropometric measurements of height and weight. RESULTS: Among schoolchildren who performed a recommended level of physical activity, there was no significant difference in perceptions according to weight status. However, among those who did not practice physical activity, obese participants had significantly less positive perception. Overweight and obesity significantly increase the risk of negative perception of physical activity practice among participants who do not do the recommended level of physical activity. However, this association becomes non significant among those who practice recommended level of physical activity. The same findings were observed after adjustment by age and sex. CONCLUSION: Negative attitudes among inactive children may favor the development of a vicious circle perpetuating physical inactivity among normal-weight and overweight children.